ANALISIS MINAT BELAJAR SISWA MELALUI MEDIA GAMBAR SISWA KELAS 2 SDN SAWAH BESAR 01 - Noer Cahyani Hidayah; Khusnul Fajriyah; Kartinah (STKIP Subang, 2023)
This study aims to analyze the learning interests of grade 2 students at SDN Sawah Besar 01 towards media images. This research belongs to the type of qualitative research with a descriptive method approach. Subjects taken in this study were 6 students with high, medium and low categories. Data collection techniques were in the form of document study tests and interviews with students who were used as research subjects. The results showed that the learning interest of the 2nd grade students at SDN Sawah Besar 01 had high enthusiasm in the learning process in using media images, students had a feeling of joy and were active in the learning process. Learning media that is suitable for students, especially in the lower classes, is using picture media. The problem that arises in grade 2 students at SDN Sawah Besar 01 is the lack of interest in learning in some students during the learning process using media images, therefore the importance of attractive media images is to increase student learning interest.